Effects of the povidone-iodine (PVPI) in treatment of bacterial peritonitis induced in rats - Araujo,Ivana Duval de (2010)
PURPOSE: To evaluate the effectiveness of the use of the povidone-iodine (PVI) added to the liquid of wash of the peritoneal cavity in the reduction of bacterial absorption and in the remainder non-phagocyted bacteria in the circulating blood of rat. METHODS: Thirty four Wistar females rats were used, distributed in the following groups: A (n=10), non-treated; B (n=9), wash of the peritoneal cavity with solution of PVI to 1% in saline solution; C (n=15), wash of the cavity with saline solution. After anesthesia, it was made intraperitoneal infusion of solution of Escherichia coli labeled with 99mTc containing 10(8) CFU/ml. After 40 minutes, it was made the treatment, in the group A, manipulation of the viscera; in the group B, irrigation of the peritoneal cavity with warm solution of 1% PVPI to 37,5ºC, and in the group C irrigation with warm saline (37,5ºC). After 15 minutes of the treatment, blood samples and fragments of liver, spleen and lung was obtained for count of the radioactivity, and animals killed by abdominal aorta section. There were determined the bacterial absorption index and the remainder index in the bloodstream. RESULTS: Of the total of bacteria infused in the peritoneum, there was absorption of 0,92% (0,14% to 2,13%) in the animals of the group A (controls), 0,49% (0,18% to 0,71%) after use of topical PVPI (group B) and 0,80% (0,04% to 3,8%) after wash with saline solution (group C). There was significant reduction of the absorption when compared the treated animals with PVPI and the controls (p=0,003). Of the total of bacteria absorbed for the circulatory current, the percentile amount of bacteria non-phagocyted in the outlying blood was of 2,9% (1,1% to 17,7%) in the control group, 15,2% (8,3% to 21,4%) in those treated with PVPI (group B) and 6,9% (0,8% to 29,7%) after wash with saline solution (group C), with difference among controls and treated with PVPI (p=0,01). CONCLUSION: The wash of the cavity peritoneal of mice with solution containing PVPI showed to be capable to reduce the absorption of bacteria by peritoneum of rat; however it seems to interfere with the function of the phagocytic cells for the observation of the increase of viable bacteria in the outlying blood of those animals.